Pawn Company Internal Factor Analysis - Satya Winarah; Rina Anindita (Journal of Social Science, 2023)
In the midst of competition in the conventional pawn business after the COVID-19 pandemic, a strategy is needed to attract consumers to do their pawn transactions. We offer a solution by providing an application where consumers do not need to come to the shop to pawn their goods anymore. With an easy- to-use application by all groups and pick-up systems for the goods that wanted to be pawned, it is a new breakthrough in the business. Internal factor analysis is carried out to determine the advantages of the pawn application based on the resources and capabilities that the company have in order to determine the right competitive strategy. The analysis of those internal factors in the pawn business is carried out through demand analysis, analysis of competition, resource and capability assessment, VRIO analysis, and also strength and weakness analysis by matrix. Based on these analyses, it is known that there are several strengths of this business that can become the competitive advantages and weaknesses that must be improved in order to compete better with other pawn companies.